The Relationship Between Students Anxiety and Their English Presentation at SMK GKST 2 Tentena: Relationship Between Students Anxiety and Their English Presentation at SMK GKST 2 Tentena - Kalepu, Rosliana; Pelenkahu, Noldy; Liando, Nihta V. F (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study investigated the relationship between student anxiety and English presentation performance among 32 eleventh-grade students at SMK GKST 2 Tentena. Using a quantitative approach with a correlational descriptive design, the data of this study was collected through a modified Foreign Language Class Anxiety Scale (FLCAS) questionnaire and direct observation of student presentations. Results revealed that 84.4% of participants experienced high anxiety, 12.5% moderate anxiety, and 3.1% severe anxiety when presenting in English. Regarding presentation performance, 40.63% of students demonstrated good performance, 37.5% fair, 18.75% poor, and 3.12% excellent. Pearson correlation analysis yielded a strong positive correlation (r = 0.840) between student anxiety and English presentation performance, indicating that higher anxiety levels significantly impacted students' ability to present effectively in English. These findings suggest that addressing anxiety factorsÃ¢â‚¬â€such as fear of making mistakes, negative evaluation, lack of preparation, and limited language proficiencyÃ¢â‚¬â€could improve students' English presentation skills. The study recommends implementing strategies like adequate preparation, positive mindset development, English skill improvement, creating supportive environments, and teaching relaxation techniques to help students overcome anxiety and enhance their presentation performance.